A Clinical Study For The effectiveness of treatment by psychodrama and alleviating the symptoms of phobias in children through a case study (Damascus University Journal of educational and Psychologyical sciences, 2021)
This research aims to identify the symptoms of phobias in children, through a case study of a child who showed Phobia response because of its exposure to a terrifying experience several times. She was 9 years old.The current research also aims to release the effectiveness of the counseling program followed in the symptomatic treatment of phobias. The research depended on the following instruments:• Phobias Scale directed to the people prepared by the researcher scale.• Indicative Programme practice, prepared by the researcher.Search has been implemented within the spatial limits in a school in the city of Damascus for basic education, the first cycle in the temporal limits of the extended (1/10/2016) to (01/30/2017) .The study found a number of findings, including;It turned out to be more severe symptoms, which appeared on the subject of the case study, the physiological symptoms (as speed breath, stuttering to speak or not to speak, pallor).Followed by side symptoms (avoid dark and absolute loneliness).Effectiveness of the existing program to reduce the artistic sensitivity gradually through exposure to psychodrama to remove phobia symptoms in the case.
Keywords: A Clinical Study For The effectiveness of treatment by psychodrama and alleviating the symptoms of phobias in children through a case study